UJI EFEKTIVITAS EKSTRAK PIROLISIS Nicotiana tabacum L. var Virginia TERHADAP BAKTERI Pseudomonas aeruginosa ATCC 27853 - Sheila Azelya Fernanda (2020)
Indonesia is a nation with high tobacco production and its different kind of varieties on the islands of Bali, Sumatra, Java and Nusa Tenggara. At the moment, the main product of tobacco is cigarette. In addition, tobacco can also be used in the health field as herbal medicine. Tobacco plant, especially the leaves, contain active compounds such as flavonoids , alkaloids, and terpenoids which are antimicrobial. This study aimed to determine the effectiveness of tobacco extract inhibition perfomance on the growth of Pseudomonas aeruginosa bacteria. This study used experimental research design with tobacco extract samples obtained from the Department of Chemical Engineering, University of Indonesia with concentrations of 20%, 40%, 60%, 80% and 100%. The extraction method used was pyrolysis method. Then, the antimicrobial test method used in this study was the well diffusion method on Mueller Hinton Agar medium. One-Way ANOVA test result with p = 0.001, indicated there was antimicrobial effectiveness of tobacco extract on the growth of Pseudomonas aeruginosa. The largest inhibition zone diameter was found at the concentration of 80%, which was 8.9 mm. The largest inhibition was included in the category of moderate inhibition.